Awareness of prostate cancer and its screening tests in men in the Middle East: A systematic review and meta-analysis - Nawaf S.A. Mohamed; Joud M.O. Asfari; Samar M.A. Sambawa; Rima M.D. Aljurf; Kholoud A.A. Alsaygh; Assad M. Arafah (Journal of Family and Community Medicine)
Prostate cancer (PCa) is a significant health issue characterized by the uncontrolled growth of cells in the prostate gland primarily affecting men 50 years old or older. The aim of this research was to assess the level of knowledge and attitudes of men in the Middle East towards PCa. A comprehensive search strategy in major databases from the date of first publication on this topic to April 2024 was conducted of cross-sectional studies assessing the knowledge and attitudes of adult men in the Middle East toward PCa. Data on the study’s methodology, participant characteristics, and outcomes related to the knowledge of PCa and attitudes towards PCa were extracted and analyzed using the comprehensive meta-analysis software. The Newcastle–Ottawa Scale was used for quality assessment. The meta-analysis of 26 studies revealed significant heterogeneity among studies, with an overall rate of previous education on PCa at 76.3% (95% confidence interval [CI]: 61.2%– 86.8%), but a much lower rate of education on PCa screening at 20.5% (95% CI: 7.2%–46.2%). Knowledge of PCa, its screening tools, symptoms, risk factors, and treatments, as well as attitudes towards PCa screening, varied widely, with knowledge rates of 50.5% for PCa, 32.3% for screening tools, 45.5% for symptoms, 49.4% for risk factors, and 58.4% for treatments. The rate of favorable attitude towards PCa screening was reported at 50.0% (95% CI: 36.7%–63.3%). The Middle East has some understanding of PCa but there is little knowledge of screening techniques, symptoms, risk factors, and treatments. To improve early detection and patient outcomes, comprehensive education and culturally sensitive communication strategies are necessary.